METODE KRITIK HADIS JALÂL AL-DÎN AL-SUYÛṮÎ - Ali, Innaka Kamal (AL ISNAD: Journal of Indonesian Hadith Studies, 2023)
The main discussion in this study is about al-Suyûṯî’s hadith criticism and the method he used in his hadith criticism. The method used in this study is a descriptive-analytical method by searching to libraries data used with the aim of revealing how is the method of criticism of the hadith of Jalal al-Dîn al-Suyûṯî in the context of the steps taken and what are the implications of the criticism of the hadith of al-Suyûṯî, while the data that is criticized and analyzed comes from the book of fatwa al-Suyûṯî entitled al-H̱âwî lî al-Fatâwâ the contents of which are al-Suyûṯî’s critique of hadith, as well as several of al-Suyûṯî’s other works, especially in the field of hadith science. The conclusions of this study are: First, in criticizing a hadith al-Suyûṯî takes steps that include his criticism of sanad and matan. Second, al-Suyûṯî’s main method of criticizing a hadith is 1. Strictly criticizing the narrators; 2. Criticizing by comparing matan; 3. Criticizing by analyzing reality and historical facts; 4. Criticizing by basing his criticism on the opinions of another hadith critic; 5. Presenting theories and rules in the science of hadith that support his criticism of hadith. Third, the criticism of the hadith of al-Suyûṯî has implications for the development of the study of hadith criticism in general, so that scholars make his criticisms and opinions as references in their books